1998
DOI: 10.1080/13623699808409383
|View full text |Cite
|
Sign up to set email alerts
|

Surviving the impossible: The long March from Srebrenica. An investigation of the possible use of chemical warfare agents

Abstract: In July 1995 about 15,000 people attempted to walk from the enclave of Srebrenica to free territory in Bosnia. Two-thirds were captured or killed. Many of the remainder experienced hallucinations on the march, leading them to believe they were the victims of chemical weapons. This paper reports extended structured interviews with 35 survivors, including three doctors, carried out a year later on behalf of Human Right Watch. The literature on the likeliest CW agent, 3-quinuclidinyl benzilate (BZ), and on stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Hallucinations occurring in victims of predatory aggression are well-described from the Rwanda genocide, the Srebrenica massacre and the Holocaust (see for example 74 for the Srebrenica massacre), but we were unable to identify classical NDEs in genocide survivors. Of note, however, we did find examples from each of these three events when (conscious) death feigning enabled individuals of Tutsi, Bosnian Muslim or Jewish heritage to survive mass murder against all odds.…”
Section: Discussionmentioning
confidence: 82%
“…Hallucinations occurring in victims of predatory aggression are well-described from the Rwanda genocide, the Srebrenica massacre and the Holocaust (see for example 74 for the Srebrenica massacre), but we were unable to identify classical NDEs in genocide survivors. Of note, however, we did find examples from each of these three events when (conscious) death feigning enabled individuals of Tutsi, Bosnian Muslim or Jewish heritage to survive mass murder against all odds.…”
Section: Discussionmentioning
confidence: 82%
“…After the literature on the likeliest CW agent, 3-quinuclidinyl benzilate (BZ), and on stress as a cause of hallucinations was reviewed, CW exposure could not be ruled out. It was concluded that the hallucinations can be ascribed to the consequence of multiple stress: artillery attacks, exhaustion due to lack of sleep, starvation, thirst and the effects of drinking unpurified water (34). Despite the fact that Srebrenica was a United Nations (UN) safe zone, the murder of 7,000-8,000 Bosniak men was not prevented.…”
Section: Srebrenicamentioning
confidence: 99%
“…However, the marked hallucinogenic actions of QNB led to its potential use as a CWA (Marshall, 1979). In July 1995, the Yugoslav People's Army allegedly used an incapacitating agent that caused hallucinations and irrational behavior against Bosnian refugees fleeing the town of Srebrenica (Hay, 1998). While many believe that this incapacitating agent was QNB, there is no evidence to support this allegation.…”
Section: -Quinuclidinyl Benzilatementioning
confidence: 95%